METAFORA LEKSIKAL PADA NOVEL MARIPOSA KARYA LULUK HF - Purba, Darmaweni; Syahrani, Agus; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to describe the lexical metaphors contained in the novel Mariposa by Luluk HF using a descriptive method and qualitative form. The data source for this study is in the form of documents from the novel Mariposa by Luluk HF. The novel used is Mariposa novel by Luluk HF. The research technique employed is documentary study technique, with the tools used in the form of laptops and writing tools. The results indicate three types of lexical metaphors in the novel Mariposa by Luluk HF which is lexical metaphors in Mariposa novel by Luluk HF, namely lexical metaphors with the concept of noun - noun as many as one clause, lexical metaphors with the concept of noun - verb as many as 13 clauses, and lexical metaphors with the concept of noun - adjective as many as ten clauses. Lexical metaphors with the concept of noun - verb are most frequently encountered in Luluk HF's Mariposa novel because in this type of lexical metaphor, an event is observed as something that motion or lives and something that is subjected to certain actions or processe